Mario Saltarelli & Dieter Wagner, Diachronic studies in Romance linguistics. Mouton, The Hague-Paris, 1975; 244 pp. (Janua linguarum, Series practica, 207). - Perissinotto, Giorgio Sabino Antonio (Nueva Revista de Filología Hispánica (NRFH), 1979)
Se reseñó el libro: Diachronic studies in Romance linguistics.